Relapses Children's Acute Lymphoblastic Leukemia, Single Center Experience - Weronika Stolpa; Magdalena Zapała; Bartosz Zwiernik; Agnieszka Mizia-Malarz (MDPI AG, 2022)
The prognosis in children and adolescents with relapsed ALL, despite intensive therapy, including hematopoietic stem cell transplantation, is still challenging. This study aims to analyze the incidence of relapsed ALL and survival rates in correlation to the risk factors. Materials and methods: 125 pediatric patients with ALL diagnosed in our department between 2000-2018; age 1-18 years old (median 6.4); female 53.6% vs. male 46.4%. Results: 19 pts (15.2%) were diagnosed with a relapse. Three pts (15.8%) had been diagnosed with very early relapses (2/3 T-ALL), 12 pts (63.1%) as an early relapse, and 4 pts (21.1%) as a late relapse. Bone marrow was the most frequent relapses localization. The five-year survival has been achieved by six patients (31.6%). A significant difference was found in regard to the five-year overall survival and relapse type (p < 0.05). The group with very early relapses (3/3; 100%) has not reached the five-year survival. Conclusions: 1. The main prognostic factor in children's ALL relapses is still the time of the onset of the relapse. 2. The T lineage acute lymphoblastic leukemia is a worse prognostic factor. 3. The analysis of the above relapse risk factors alongside cytogenethic markers and flow cytometry or polymerase chain reaction minimal residual disease is very important for first-line chemotherapy improvement and a more personalized choice of therapy for ALL patients.